2011
DOI: 10.1002/elan.201100292
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalysis at Salt – Cotton – Electrode Interfaces: Preconcentration Effects Lead to Nano‐Molar Hg2+ Sensitivity

Abstract: Cotton is employed as a sample absorbent which is analysed sandwiched between a glassy carbon electrode and ammonium nitrate salt in a humidified argon atmosphere (ca. 80 % relative humidity). Exploratory experiments show that well-defined voltammetric responses for the Fe(CN) 6 3À/4À redox system pre-absorbed into cotton are observed. Experiments with gold plating solution absorbed into cotton reveal the microscopic regions (cotton -glassy carbon contact points) of electrochemical activity where gold micropar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In recent reports the use of salt|electrode contact processes has been demonstrated for the case of salt surface immobilized redox systems, for palladium catalyst coated electrodes, and for textile-coated electrodes . In this study it is demonstrated that ammonium nitrate salt crystals can be used as a “thin film electrolyte phase” also in a nonpolar solvent such as hexane to electrically connect the working electrode and a counter-reference electrode (see Figure B).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In recent reports the use of salt|electrode contact processes has been demonstrated for the case of salt surface immobilized redox systems, for palladium catalyst coated electrodes, and for textile-coated electrodes . In this study it is demonstrated that ammonium nitrate salt crystals can be used as a “thin film electrolyte phase” also in a nonpolar solvent such as hexane to electrically connect the working electrode and a counter-reference electrode (see Figure B).…”
Section: Introductionmentioning
confidence: 75%
“…In recent reports the use of salt|electrode contact processes has been demonstrated for the case of salt surface immobilized redox systems, 15 for palladium catalyst coated electrodes, 16 and for textile-coated electrodes. 17 In this study it is demonstrated that ammonium nitrate salt crystals can be used as a "thin film electrolyte phase" also in a nonpolar solvent such as hexane to electrically connect the working electrode and a counterreference electrode (see Figure 1B). The resulting salt|electrode contact points allow solvent flow experiments and provide unique reaction environments for redox processes, involving for example decamethylferrocene metal complexes, as well as for bulk metal deposition from a Au(III) precursor solution in toluene.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Paper and cellulose remain popular substrates for new types of electroanalytical methods based on micro-fluidic processes/systems on disposable sensors [9,10]. Nano-cellulose materials have opened up further opportunities in electroanalysis [11] with pure cellulose [12] or composite films [13,14] being readily re-constituted or regenerated, for example on ITO electrode surfaces [15]. Surface-modified nanocrystalline cellulose whiskers have been re-constituted into redox active films with electron transfer occurring between the ferrocene grafts along the nanocrystal surface [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the traditional liquid electrochemistry (with metal/liquid interfaces) has been expanded to wet (aerosol containing) air by bridging the electrode system with salt containing fabric. , Accordingly, we decided to carry out hydrogen peroxide detection in aerosol using a salt bridged electrode system.…”
mentioning
confidence: 99%